Implementasi AI dalam Peningkatan Efektivitas Kepemimpinan di SMK YPKK 2 Sleman: Implementation of AI in Improving Leadership Effectiveness at SMK YPKK 2 Sleman - Umi Maslakhah; Saryanto Saryanto (ITScience (Information Technology and Science), 2024)
This study aims to examine the application of artificial intelligence (AI) technology in improving leadership effectiveness at SMK YPKK 2 Sleman. Resource managers and decision-makers face more complex problems in the digital era. As a result, it is necessary to have a proper plan to ensure that the available technology allows for fast and accurate decision-making. Optimizing time management, data analysis for smarter decision-making, and communication and coordination are just some of the challenges that principals can overcome with new solutions offered by AI. A qualitative approach was used in this study, which involved conducting in-depth interviews, observing participants, and analyzing relevant documents. This study found that AI can be very beneficial for school administration by automating administrative tasks, improving data-based insights, and generally improving leadership performance. However, there are also obstacles in implementing AI, including issues of technology readiness, human resource competency, and school culture adaptation to digital transformation. In order to be more creative in managing technology-based school management, this study recommends that principals and staff receive training and improve their talents. We can optimize AI to build adaptive and responsive leadership to the dynamics of today's education with better technical and human resource readiness.